Inflated Portable Cold Storage House with Solar Cells as facilities to support the fisheries production and marketing - Ikhsan Setiawan, M; Dhaniari, Iswachyu; Hasyim, Cholil; ., Yuniningsih; Abdullah, Dahlan; Nugraheni Sri Lestari, Veronika; Mulyo Utomo, Wahyu; Sukoco, Agus; Wiwoho Mudjanarko, Sri; Alimudin, Arasy; Harmanto, Dani; Saleh Ahmar, Ansari (International Journal of Engineering and Technology, 2018)
The global fish production currently reaches 158 million tons to 91.3 million tons. However the largest contribution is provided by the fisheries sector.Â  An estimated 136.2 million tons of fish are used directly for consumption and then for fish and livestock. In the fishery sector, Indonesia was ranked second after China, while in the fish cultivation sector Indonesia was ranked fourth after China, India, and Vietnam. The result of increasing exports reached 35.4 billion dollars in 2012. The Technology Inflated Portable Cold Storage House with Solar Power as facilities to support fisheries production and marketing, can be built and applied in a residential location/ specific housing easily, safely, quickly and lightly (0,55mm PVC Tarpaulin). The development program of this technology in supporting fisheries production and marketing meet the requirements of strength, speed, flexibility and comfort. This technology also increased the absorption of the National Fish stock. Specific targets on this research is to provide Cold Storage House Prototype with solar in supporting fisheries production and marketing with cheap and profitable so that can be mass-produced. This research used experiments and action research. The process of research is starting with the development of the design, manufacture, testing and repair of Inflated Portable Cold Storage House with Solar Power Prototype, included first, a technical test of strength and endurance of Portable inflated Structure materials to the weather; second, testing the speed of the manufacture, transportation, assembly, installation, disassembly of Portable Inflated Structure; third, testing temperature, humidity and air pressure in the Inflated Portable Cold Storage House with Solar Power; fourth a technical test, related to the fishery from frozen and market in Inflated Portable Cold Storage House with Solar Power in order to obtain hygienic, inexpensive and profitable fisheries.Â